2018
DOI: 10.1007/s40519-018-0570-6
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric evaluation of the English version of the Düsseldorf Orthorexie Scale (DOS) and the prevalence of orthorexia nervosa among a U.S. student sample

Abstract: Descriptive study, Level V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
75
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 37 publications
10
75
1
3
Order By: Relevance
“…Moreover, individuals following a vegetarian diet, compared to individuals following an omnivorous diet, are more informed than others about healthy eating, know more about healthy eating than other people, prepare food in the most healthful way and are convinced that their diet is more healthy than most diets, their diet is better than other people's diets and their eating habits are superior to others (the EHQ's items [31] related to knowledge of healthy eating). Our results are consistent with previous research using the same questionnaire (EHQ) [20,33]. Other studies (using another methods) have also indicated that individuals following a vegetarian diet reported more orthorexic behaviors than those who follow an omnivorous diet [17,34,35].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, individuals following a vegetarian diet, compared to individuals following an omnivorous diet, are more informed than others about healthy eating, know more about healthy eating than other people, prepare food in the most healthful way and are convinced that their diet is more healthy than most diets, their diet is better than other people's diets and their eating habits are superior to others (the EHQ's items [31] related to knowledge of healthy eating). Our results are consistent with previous research using the same questionnaire (EHQ) [20,33]. Other studies (using another methods) have also indicated that individuals following a vegetarian diet reported more orthorexic behaviors than those who follow an omnivorous diet [17,34,35].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the change in eating behaviors seen in people with ED is usually associated with the perceived "fattening" effect [60], which could have contributed to the more frequent consumption of meat and meat products and reduced consumption of sugar-rich and refined products. It can also be assumed that, in people with both ON tendency and ED symptoms, the occurrence of the former was not associated with the use of a vegetarian or vegan diet [56,61].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that more than half of the ED patients had followed a vegetarian diet in the past, while almost 24% of them are currently vegetarians [63]. In addition, a relationship has been observed between ON tendency and the use of vegetarian and vegan diets [56,61]. Some researchers suggest that vegetarianism and veganism can be a socially acceptable way to avoid certain foods or certain eating situations and used as a mask to hide ED [24,62,63].…”
Section: Discussionmentioning
confidence: 99%
“…DOS zawiera łącznie 21 pozy-cji, jednak stosowany jest też w krótszej formie (10-item-DOS). Kwestionariusz wykorzystano kilkakrotnie w badaniach niemieckich (Barthels i in., 2015;Barthels, Meyer, Huber, Pietrowsky, 2017;Rudolph, 2018) i przetłumaczono na język angielski w populacji amerykańskich studentów (Chard, Hilzendegen, Barthels, Stroebele-Benschop, 2018). Kwestionariusz okazał się trafny i rzetelny, lecz autorzy adaptacji wskazują na pewne ograniczenia związane z wykorzystywaniem narzędzia w innych populacjach (także anglojęzycznych).…”
Section: Narzędzia Diagnostyczneunclassified